Antioxidant and antihyperglycemic activity of the medicinal specie Oreocallis grandiflora (Lam.) R. Br., in southern Ecuador [Actividad antioxidante y antihiperglucemiante de la especie medicinal Oreocallis grandiflora (Lam.) R. Br., al sur del Ecuador] - Alejandro, M. (2012)
In this study we evaluated the antioxidant and antihyperglycemic activity in vitro of the extracts obtained with solvents: hexane, ethyl acetate and methanol, of the medicinal plant Oreocallis grandiflora (cucharillo), collected in the Saraguro indian community of the province Loja, southern Ecuador. The antioxidant activity was evaluated by the tests: DPPH, FOLIN-CIOCALTEU and ?-CLAMS, while the antihyperglycemic activity was determined by inhibition assay ?-amylase and ?-glucosidase. The samples were diluted to different concentrations and the reading was performed in a UV spectrophotometer, using as positive control ?-tocopherol for DPPH and Folin-ciocalteu test, trolox for ?-CLAMS test, and Glucobay for testing ?-amylase and ?-glucosidase.The results are expressed as IC50, these show that the methanol extract of Oreocallis grandiflora has inhibitory effect on ?-amylase, the IC50 is 109 ?g/ml, compared to 126 ?g/ ml of Glucobay. It also shows inhibitory effect on ?-glucosidase, the IC50 is 3 ?g/ml compared to 1316 ?g/ml of Glucobay. It also shows antioxidant activity, its IC50 is 15 ?g/ml compared to 5 ?g/ml of ?-tocopherol. © 2013 Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas.